October sky (Universal City, CA : Universal Studios, 1999)
True story of a young boy growing up in Coalwood, West Virginia during the 1950's who dreams of building rockets
Based on the book "Rocket Boys" by Homer H. Hickam, Jr
Originally produced as a motion picture
PG
Music by Mark Isham ; screenplay by Lewis Colick ; directed by Joe Johnston
Jake Gyllenhaal, Chris Cooper, Chris Owen and Laura Dern
Canadian home video rating: 14a.
Keywords: Hickam, Homer H., -- 1943- -- Drama; Films for the hearing impaired; Feature films; DVD-video discs -- 2004.; West Virginia; Coalwood (W. Va.) -- Social life and customs; Feature films